Menggali Kekayaan Linguistik: Variasi Penyapaan dalam Interaksi Verbal Siswa Menengah Pertama - Arman Arman,; Andi Paida,; Muhammad Dahlan, (Jurnal Bintang Pendidikan Indonesia, 2023)
This research aims to discuss the greeting patterns of the Indonesian language used by junior high school students at Unismuh Makassar. The data in this study consists of the oral utterances of Unismuh Makassar junior high school students that contain greetings or various forms of greetings spoken by the speaker. The research method employed is descriptive qualitative. The primary data is information obtained directly through observation of student conversations and interviews related to the required data, consisting of 10 questions. Meanwhile, the secondary data is information obtained from other sources regarding the junior high school students of Unismuh Makassar. The observation method technique is used in this research. The results of this study are as follows: (1) At Unismuh Makassar Junior High School, students' multilingual verbal interactions reflect a combination of Makassar and Indonesian languages. Students use greetings such as "mauka," "kakak," "adik," "Ibu," and "Bapak," as well as informal greetings like "Cika," "Beb," "Eh," and "Weh." These greetings indicate a variety of contexts, from formal forms that show respect to informal ones that indicate closeness. (2) Unismuh Makassar junior high school students demonstrate the integration of Indonesian and Makassar languages in their greeting patterns. They combine both languages, such as using "mauko" when meeting friends. In formal situations, like interacting with teachers, students use the Makassar language as a form of respect. This reaffirms the role of both in students' daily communication.